Genetics and Reading Disabilities - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1987)
Psychologists and psychiatrists at the University of Surrey, Guildford, Surrey, and the Hospital for Sick Children, Great Ormond Street, London, UK studied the reading skills of 285 pairs of 13 year-old twins using standardized measures of intelligence, reading and spelling ability and correlations in monozygotic and same-sex dizygotic twins.